Business Strategy of the Travel Agency - Heřmánek, Lukáš; Tyll, Ladislav; Pernica, Karel; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2016)
The aim of this work is to carry out strategic analysis of the company British Studies Agency, s.r.o with emphasis put on improvement of its current state and advise the possible strategies for future growth. In the theoretical part basic terms of the strategic analysis will be mentioned and then used in the practical part. It is focused on actual strategy of the travel agency British Studies, where PEST and Porters Five Force Model are used as a part of the external environment. The analysis of the internal capabilities and resources will be devoted to VRIO and both environments analyzed with overall SWOT.
Vedoucí práce: Ladislav Tyll
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: corporate finance and management [obor bakal. práce]; bakalářské práce; bachelor's theses